Examining the immanent dilemma of small states in the Asia-Pacific: the strategic triangle between New Zealand, the US and China. Issue 1 (2nd January 2019) - Steff, Reuben; Dodd-Parr, Francesca
ABSTRACT: Small states throughout the Asia-Pacific are confronted by a growing dilemma over how to balance their traditional security ties with the US and rapidly growing trade with China. This gives Washington and Beijing potential leverage over small states to use within their competition with one another. This article explores the implications of this for New Zealand – a small South Pacific state that prides itself on maintaining an independent foreign policy. Situated within the small state literature, it utilises a material-based strategic triangle to illustrate the fundamental facets of New Zealand's position. Relatedly, the article examines how Wellington has managed its burgeoning relations with China and the US over the past decade and critically considers New Zealand's independent foreign policy. It finds that New Zealand has adopted a mixed set of strategies to manage its position between the US and China, closely aligning itself with Washington while remaining nonaligned on some key security issues in the Asia-Pacific region. New Zealand has certainly not opted for neutrality. The article concludes that New Zealand and other small states must remain vigilant, may want to consider alternative strategies of alignment, and outlines a number of areas where additional research could prove fruitful.